Surfactant Distribution on the Liquid Surface Above an Approaching Particle - Alexander A. Nepomnyashchy (Colloids and Interfaces)
The axisymmetric distribution of an insoluble surfactant on the liquid surface above a particle rising towards the surface has been considered. Under the assumption that the surface is fully covered by the surfactant, an analytical expression for the quasistationary surfactant distribution is found. The limits of the assumption validity are discussed. The conditions for the appearance of a region free of the surfactant is found.